(untitled) (Al-Academy, 2023)
Theater is a renewed art until this moment, and it does not stray from its components from life and its spaces in general, but rather is derived from them according to characteristics and directions intended to differ based on finding other, more effective solutions, Therefore, the research entitled (Extractive treatments of the space between tradition and contrast in contemporary theater) consists of four chapters. The first chapter came under the title (the methodological framework). Where he dealt with the research problem and then the importance of the research and the goal of the research as well as the objective, temporal and spatial limits of the research, In addition to defining the terminology and then finding the procedural term that the researcher deduced through his reading of the sources, references and opinions he reached. As for the second chapter, entitled (Theoretical Framework), the researcher divided this chapter into the following sections: The first topic: the concept of space in theatrical performance. The second topic: Tradition and contrast in contemporary theatrical performance. Then the previous studies and the results of the theoretical framework of indicators to conclude that chapter. As for the third chapter, entitled (Research Procedures), the researcher dealt with: the research community - the research sample - the research method - the research tools - the sample analysis entitled (women’s playing). With regard to the fourth chapter, which is entitled (Conclusions and Conclusions), the researcher reached the results and then identified the conclusions he reached, and then put forward the proposals and recommendations, then a list of sources and references